Diverse new plasmid structures and antimicrobial resistance in strains isolated from perianal abscess patients - Xu, Zhen; Shi, Lulu; Meng, Tao; Luo, Mei; Zhu, Jiaming; Wang, Mingyu; Shen, Wenlong (Frontiers in Microbiology, 2024)
Plasmids, the most important and versatile bacterial extrachromosomal DNA molecules, have been a central topic for bacterial genetics and biology. However, the inability of short-read high-throughput sequencing methods to reliably assemble plasmids makes it difficult to investigate the diversity of plasmid structures and functions. In this work, we used the long-read Nanopore sequencing method to address this issue, by producing high quality whole genome sequences of 33 bacterial strains from 11 perianal abscess-suffering patients. Successful high quality assemblies were generated with this method, including 20 perfect assemblies out of 33 genomes. A total of 47 plasmids were identified from the bacterial strains, including 12 unique, newly identified, high quality circular plasmids. These plasmids were further subject to structural analysis, leading to the finding of significant diversification from previously known plasmids, suggesting the diversity of plasmid structure and function. Particularly, two mcr-10.1-harboring conjugative plasmids were found from Citrobacter portucalensis and Enterobacter kobei, which were not previously reported. This works shows the feasibility of using long-read sequencing to identify plasmids, and the high diversity of plasmid structure and function that awaits further surveillance.